(untitled) (American Journal of Islam and Society, 2002)
Combining in-depth historical and socio-political analyses of the American food industry with an easy-flowing language style, Fast Food Nation is nearly impossible to put down. Mind-boggling in scope, yet as intimate as one’s own kitchen, this book allows the reader to grasp the true horror of the global food situation. Schlosser provokes both laughter and tears, ultimately inspiring the reader to engage in the "higher jihad" of controlling one’s appetite with the understanding of how personal consumer choices have political consequences. Section One, "The American Way," takes us through four chapters. The first, entitled "The Founding Fathers," talks about how the mass production of the automobile transformed post-WWII American society and its land scape, and introduces us to the hard-working businessmen who gave fast food a permanent place in the car culture, replacing the lovely countryside with a nearly identical, ugly sprawl of fast food restaurants, subdivisions, and strip malls in every town. Chapter 2, "Your Trusted Friends," explains the appeal of the fast food industry to children and adults longing for their past childhood through the use of toys and mascots such as Ronald McDonald and Taco Bell’s talking dog. Gearing advertisements to the psychology of children has become a big business. Al I the major toy crazes such as Beanie Babies and Pokemon have been promoted by fast food chains. Cross-promotions extend to cartoons, movies, amusement parks, and now schools. Due to funding shortages, many schools have started promoting brand names of fast food and soda companies, whose ads now cover school hallways, buses, and even rooftops, while the products are sold to children during school hours ...